2011
DOI: 10.1038/nn.2805
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila model for alcohol reward

Abstract: The rewarding properties of drugs contribute to the development of abuse and addiction. Here we present a new assay to investigate the motivational properties of ethanol in the genetically tractable model, Drosophila melanogaster. Flies learn to associate cues with ethanol intoxication and, although transiently aversive, the experience leads to a long-lasting attraction for the ethanol-paired cue, implying that intoxication is rewarding. Temporally blocking transmission in dopaminergic neurons revealed that fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
291
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 212 publications
(322 citation statements)
references
References 45 publications
10
291
0
Order By: Relevance
“…However, a critical difference is that stm-and ltm-PAM neurons seem to signal different properties of the same reward, again pointing to more complex representation of the sugar reward. It would be interesting to compare neuronal representations of different rewarding stimuli, such as ethanol (51) and water (41,52). An important future question would be to understand physiological mechanisms by which the MB computes the distinct dopamine inputs to control approach behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a critical difference is that stm-and ltm-PAM neurons seem to signal different properties of the same reward, again pointing to more complex representation of the sugar reward. It would be interesting to compare neuronal representations of different rewarding stimuli, such as ethanol (51) and water (41,52). An important future question would be to understand physiological mechanisms by which the MB computes the distinct dopamine inputs to control approach behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Similar temporal transitions have been found in feeding choice (58), where flies initially choose sugars according to sweet taste, but later prioritize caloric contents. Similarly, ethanol exposure initially acts as an aversive reinforcer, but eventually turns into reward and induces LTM (51). The sequential regulation of appetitive behavior by the same stimulus may be conserved across relevant appetitive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is said that such an experience is rewarding or positively reinforcing to the fly. By using such conditioned odor preference assays (6,7), it has been shown that flies perceive sucrose (6), water (8), alcohol intoxication (9), and mating (10) as rewarding, while noxious stimuli, such as electric shock, are perceived as aversive (6,7). These findings parallel those in mammalian systems, underscoring the relevance of reward perception and processing in flies to our general understanding of reward (11)(12)(13)(14).…”
mentioning
confidence: 90%
“…Model organisms, including selectively bred lines (8)(9)(10), offer a potentially powerful framework for genomic analyses to identify genes and their functional variants that contribute to complex disorders. The selective breeding process reduces genetic heterogeneity and enriches to high frequency variants that influence the targeted phenotype.…”
Section: Gene Identification | Selectively Bred Linesmentioning
confidence: 99%